Perbedaan Model Pembelajaran Numberhead Together (NHT) dengan Model Pembelajaran Student Team Achievement Division (STAD) Terhadap Gaya Belajar dan Hasil Belajar Tematik Siswa Kelas IV Sekolah Dasar - Yuvena Ajeng Putri Setiawan; Eunice Widyanti Setyaningtyas (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the differences between STAD (Student Team Achievement Division) learning models and NHT (Number Head Together) learning models towards learning styles and student learning outcomes. This research consists of 2 stages, namely Pretest and Posttest. The subjects were grade IV students of SD N Manggihan and class IV MI Nurul Islam Batur 02 Getasan District, Semarang Regency. Based on the results of data analysis, it can be concluded that there are differences in the use of the STAD (Student Team Achievement Division) learning model and the NHT (Number Head Together) learning model towards learning styles and student learning outcomes. The STAD (Student Team Achievement Division) learning model is better able to show the ability of learning styles and student learning outcomes, in terms of Sig. (2 tailed) is 0,000 <0.005 then Ho is rejected and Ha is accepted.